Chemically induced dimerization: reversible and spatiotemporal control of protein function in cells. (October 2015) - Voß, Stephanie; Klewer, Laura; Wu, Yao-Wen
Highlights: Novel orthogonal and reversible CID systems confer multiple layers of manipulation. Caged dimerizers allow control of protein function with spatiotemporal resolution. New applications of CID tools in dissecting signal transductions are discussed. Studies of membrane trafficking by CID in a spatiotemporal manner are described. Abstract : Small-molecule perturbation of biological systems is able to tackle biological problems that are not accessible by classical genetic interference methods. Chemically induced dimerization (CID) has been used as a valuable tool to study various biological processes. Recent years have seen tremendous progress in the development of orthogonal and reversible CID systems. These new systems allow control over protein function with unprecedented precision and spatiotemporal resolution. While the primary application of CID has been on dissecting signal transductions, new emerging approaches have extended the scope of this technique to elucidating membrane and protein trafficking.